Advertising and promotion : an integrated marketing communications perspective - Belch, George E. (George Edward), 1951-; Belch, Michael A. (McGraw-Hill Education, 2021)
"THE CHANGING WORLD OF ADVERTISING AND PROMOTION Nearly everyone in the modern world is influenced to some degree by advertising and other forms of promotion. Organizations in both the private and public sectors have learned that the ability to communicate effectively and efficiently with their target audiences is critical to their success. Advertising and other types of promotional messages are used to sell products and services as well as to promote causes, market political candidates, and deal with societal problems such as alcohol and drug abuse. Consumers are finding it increasingly difficult to avoid the efforts of marketers, who are constantly searching for new ways to communicate with them"--